HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PENJASORKES SMPN DI KECAMATAN TOHO KABUPATEN MEMPAWAH - Situmorang, Dionisius Sahalatua (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the influence of principal leadership style on the performance of secondary school teachers in Toho subdistrict Mempawah district. Research approach using quantitative approach. The population in this study were all principals and teachers of the State Junior High School junior high school teachers with 6 principals and 6 master teachers. In this study the sampling technique is saturated ie all members of the population used as a sample. Data collection techniques used questionnaires. The assumption test is normality and linearity. Data analysis was done by simple regression. The results of this study obtained the value of t arithmetic with 6.093 with a significance of 0.004 smaller than 0.05. Thus the accepted hypothesis means that there is influence of principal leadership style on the performance of teacher penjasorkes of 90.3%.Keywords: Principal Leadership Style, PerformanceTeacher Education physical sport and health